Women's Murder Club : The 17th Suspect - Patterson, James, 1947-.; Patterson, James & Paetro, Maxine; LaVoy, January ([New York] : Hachette Audio, 2018)
A series of shootings exposes San Francisco to a methodical yet unpredictable killer, and a reluctant woman decides to put her trust in Sergeant Lindsay Boxer. The confidential informants tip leads Lindsay to disturbing conclusions, including that something has gone horribly wrong inside the police department itself. The hunt for the killer lures Lindsay out of her jurisdiction, and gets inside Lindsay in dangerous ways. She suffers unsettling medical symptoms, and her friends and confidantes in the Womens Murder Club warn Lindsay against taking the crimes too much to heart. With lives at stake, the detective cant help but follow the case into ever more terrifying terrain. A decorated officer, loving wife, devoted mother, and loyal friend, Lindsays unwavering integrity has never failed her. But now she is confronting a killer who is determined to undermine it all.
Keywords: Boxer, Lindsay -- (Fictitious character) -- Fiction; Womens Murder Club (Imaginary organization) -- Fiction; Women detectives -- California; San Francisco; Fiction; Female friendship -- Fiction; Murder -- Investigation; Fiction; Police -- California; Fiction; Policewomen -- Fiction; San Francisco (Calif.) -- Fiction; Thrillers (Fiction)